Art and Belief Artists Engaged in Interreligious Dialogue. - Illman, Ruth. (Hoboken : Taylor and Francis, 2014)
''Art and Belief'' explores communication between faiths through an examination of contemporary artistic practice. The book discusses how a range of artists formulate their worldview and what motivates them to engage in dialogue. These artists are engaged in a wide range of artistic forms and practice and come to dialogue from diverse religious positions. The aim of the book is to question the assumptions of interreligious dialogue as a largely intellectual exercise in defining the religious ""other"" and to explore dialogue as a manifestation of interpersonal ethics.
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Acknowledgements; 1 Interreligious Dialogue in a Changing World; 2 Reflexive Religiosities and Complex Otherness; 3 A Creative Perspective on Interreligious Dialogue; 4 A Dialogue of Souls: Jordi Savall; 5 Exploring Estrangement: Susanne Levin; 6 Only the Idea of Snow is White: Marita Liulia; 7 When Language is Not Enough: Chokri Mensi; 8 Beauty is a Hole in the Wall: Cecilia Parsberg; 9 Inhabiting a Mystery: Eric-Emmanuel Schmitt; 10 Conclusions: The Art of Dialogue; Notes; Bibliography; Index of Names.
Print version record.
Index of Subjects.
Keywords: Artists -- Religious life; Dialogue -- Religious aspects; Dialogue -- Relations; Artists -- Religious life; Dialogue -- Religious aspects; Religions -- Relations; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books